1990
DOI: 10.1159/000261230
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Fluoride Uptake Affected by Site of Application: Comparing Sodium and Amine Fluorides

Abstract: In enamel fluoride uptake studies, the most frequently sampled site is the middle third of the buccal surface. Because different parts of the enamel surface vary in fluoride concentration, the present study investigated fluoride uptake at contrasting sites using two different topical agents. One was a neutral aqueous solution of sodium fluoride containing 2% w/w of fluoride, and the second was an aqueous solution of two amine fluorides containing 1% w/w of fluoride. The enamel of 10 pairs of clinically sound e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The results of some in situ studies, in which u demineralized enamel samples were worn by volunteers, also showed fluoride uptake was less from NaMFP-containing toothpastes than from NaF-or AmF-containing toothpastes. 27,37 The most effective Group tested in this study (Fluocaril ® Bi-Fluoré 250) contained a combination of NaF and SMFP and a total F level of 2500 ppm F. This particular combination of fluoride actives coupled with a compatible silica based abrasive system provides a high level of fluoridating efficiency.…”
Section: Fluoride Uptake Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of some in situ studies, in which u demineralized enamel samples were worn by volunteers, also showed fluoride uptake was less from NaMFP-containing toothpastes than from NaF-or AmF-containing toothpastes. 27,37 The most effective Group tested in this study (Fluocaril ® Bi-Fluoré 250) contained a combination of NaF and SMFP and a total F level of 2500 ppm F. This particular combination of fluoride actives coupled with a compatible silica based abrasive system provides a high level of fluoridating efficiency.…”
Section: Fluoride Uptake Resultsmentioning
confidence: 99%
“…Biological availability of fluoride is highly dependent on the overall makeup of the toothpaste with certain ingredients and conditions being capable of reducing or at least minimizing potential anticaries performance. 24,[27][28][29][30][31][32] Other studies have utilized surface microhardness, or combinations of fluoride uptake and microhardness, as a means to demonstrate not only how much fluoride incorporates into a tooth during treatment but also to reflect mineral changes (remineralization) that have occurred within the tooth as a function of treatments. 15,16,23,33 Almost all of these studies compared products containing single sources of fluoride.…”
Section: Introductionmentioning
confidence: 99%